If (4-k)x²+2(k+2)x+(8k+1)=0 has equal roots then find the value of k. Plzz help me....
Answers
Answered by
3
Since the roots here are equal, let both be a.
Now as we know that in a quadratic equation with coefficient of x = 1 , the product of thr roots give c and their sum gives b.
So by using that relation,
![{x}^{2} + 2 \frac{(k + 2)}{(4 - k)}x + \frac{(8k + 1)}{(4 - k)} = 0 \\ {x}^{2} + 2 \frac{(k + 2)}{(4 - k)}x + \frac{(8k + 1)}{(4 - k)} = 0 \\](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++%2B+2+%5Cfrac%7B%28k+%2B+2%29%7D%7B%284+-+k%29%7Dx+%2B++%5Cfrac%7B%288k+%2B+1%29%7D%7B%284+-+k%29%7D+++%3D+0+%5C%5C+)
So we have,
sum of roots
![a + a = 2 \frac{(k + 2)}{4 - k} \\ a = \frac{(k + 2)}{4 - k} \: a + a = 2 \frac{(k + 2)}{4 - k} \\ a = \frac{(k + 2)}{4 - k} \:](https://tex.z-dn.net/?f=a+%2B+a+%3D+2+%5Cfrac%7B%28k+%2B+2%29%7D%7B4+-+k%7D++%5C%5C+a+%3D+%5Cfrac%7B%28k+%2B+2%29%7D%7B4+-+k%7D+%5C%3A+)
And also,
product of roots,
![{a}^{2} = \frac{8k + 1}{4 - k} {a}^{2} = \frac{8k + 1}{4 - k}](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B2%7D++%3D++%5Cfrac%7B8k+%2B+1%7D%7B4+-+k%7D+)
using these two values
![{( \frac{(k + 2)}{(4 - k)}) }^{2} = \frac{8k + 1}{4 - k} \\ \\ {k}^{2} + 4k + 4 = (4 - k)(8k + 1) \\ \\ {k}^{2} +4k + 4 = 32k + 4 - 8 {k}^{2} - k \\ 9 {k}^{2} - 27k = 0 \\ 9k(k - 3) = 0 {( \frac{(k + 2)}{(4 - k)}) }^{2} = \frac{8k + 1}{4 - k} \\ \\ {k}^{2} + 4k + 4 = (4 - k)(8k + 1) \\ \\ {k}^{2} +4k + 4 = 32k + 4 - 8 {k}^{2} - k \\ 9 {k}^{2} - 27k = 0 \\ 9k(k - 3) = 0](https://tex.z-dn.net/?f=+%7B%28+%5Cfrac%7B%28k+%2B+2%29%7D%7B%284+-+k%29%7D%29+%7D%5E%7B2%7D++%3D++%5Cfrac%7B8k+%2B+1%7D%7B4+-+k%7D++%5C%5C+++%5C%5C++%7Bk%7D%5E%7B2%7D+++%2B+4k+%2B+4+%3D+%284+-+k%29%288k+%2B+1%29+%5C%5C++%5C%5C++%7Bk%7D%5E%7B2%7D++%2B4k+%2B+4+%3D+32k+%2B+4+-+8+%7Bk%7D%5E%7B2%7D++-+k+%5C%5C+9+%7Bk%7D%5E%7B2%7D++-+27k+%3D+0+%5C%5C+9k%28k+-+3%29+%3D+0)
So we have k =0 and k= 3.
Tada!!
Now as we know that in a quadratic equation with coefficient of x = 1 , the product of thr roots give c and their sum gives b.
So by using that relation,
So we have,
sum of roots
And also,
product of roots,
using these two values
So we have k =0 and k= 3.
Tada!!
Similar questions